The Role of Local Government for Local Product Processing: the Implication for Tourism Sustainability in Lok Baintan Floating Market - Deasy Arisanty; Ellyn Normelani; Herry Porda Nugroho Putro; Moh Zaenal Arifin Anis (Program Pascasarjana, 2019)
Lok Baintan floating market is the destination tourism in South Kalimantan Province. The trader activity in the floating market becomes the attractiveness of tourism activity. The diversity of good sold in the floating market becomes one of the determinants for tourism sustainability. The tourism sustainability in Lok Baintan Floating Market is the responsibility of both community and government. The objective of this research was to analyze the role of government for local product processing in Lok Baintan Floating Market to improve the tourism activity. This research is focused on local government who has the responsibility for local product processing in Lok Baintan Floating market, i.e. Tourism Agency of South Kalimantan Province, Tourism Agency of Banjar Regency, Fishery Agency of Banjar Regency, Agriculture and Farm Agency of Banjar Regency, and Head of Lok Baintan Village. The research used qualitative method, which used observation, depth interview, and document as the data collection technique. The results of the study showed that tourism activities in Lok Baintan became one of the priorities of tourism development in South Kalimantan, but not managed maximally yet. First, the Products sold in the floating market were still raw goods. Then the processing of products sold in the floating market had not been a priority of activities undertaken by local the government. Moreover, limitations of costs were the main cause of the absence of training in agricultural product processing, fishery product processing and handicraft production in the tourist area of Lok Baintan. Processing and diversity of goods sold in the floating market become a determinant of the sustainability of tourism activities in Lok Baintan Floating Market.Keywords: Government, Local product, Lok Baintan Floating Market, tourism.